2011
DOI: 10.1016/j.actamat.2011.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Study of the twinned dendrite tip shape II: Experimental assessment

Abstract: The favorable growth kinetics of twinned dendrites can be explained by their complex morphology, multiple side branching mechanisms, growth undercooling and tip morphology. Three models were proposed for the twinned dendrite tip shape: (i) a grooved tip [1] satisfying the Smith condition at the triple line; (ii) a doublon [2], i.e. a double-tip dendrite that grows with a narrow and deep liquid channel in its center; and (iii) a pointed (or edgy) tip [3], with consideration of the solid-liquid interfacial energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
(24 reference statements)
2
15
1
Order By: Relevance
“…Henry et al [10,11] made a conjecture that the twinned dendrite tip is in fact a doublon, i.e., a double-tip dendrite growing with a thin liquid channel in the center, the root of which contains the twin plane that solidifies at a solid composition close to C 0 . Recent phase-field simulations [12][13][14] as well as FIB observations [15] made by the present authors also strongly support this conjecture. On the other hand, if the propagation of twinned dendrites along the twin plane can be easily understood by branching mechanisms similar to those of regular columnar dendrites, their extension perpendicular to the twin plane, in particular the formation of new twins, remains unclear.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Henry et al [10,11] made a conjecture that the twinned dendrite tip is in fact a doublon, i.e., a double-tip dendrite growing with a thin liquid channel in the center, the root of which contains the twin plane that solidifies at a solid composition close to C 0 . Recent phase-field simulations [12][13][14] as well as FIB observations [15] made by the present authors also strongly support this conjecture. On the other hand, if the propagation of twinned dendrites along the twin plane can be easily understood by branching mechanisms similar to those of regular columnar dendrites, their extension perpendicular to the twin plane, in particular the formation of new twins, remains unclear.…”
Section: Introductionsupporting
confidence: 73%
“…[10] D. Competition Mechanisms While the competition of regular dendrites and the formation of solidification textures are well known since the work of Chalmers, [25][26][27] the growth advantage that twinned aluminum dendrites can have over regular ones under certain conditions remains unclear. The weak anisotropy of aluminum, [28] the reduced solute segregation associated with a doublon-type twinned dendrite tip, [14][15][16] and the solidification conditions (high thermal gradient, presence of convection, etc.) all play an important role.…”
Section: Twin Growth Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a condition implicitly assumes that the solid-liquid interfacial energy c s' (n) is isotropic, which is a reasonable assumption for the very weak anisotropy exhibited by aluminum alloys [17]. 1 The angle h 0 remained constant throughout the calculation and was measured in the solid; for example, an angle larger than 90°corresponds to a grooved dendrite tip. This "wetting" angle of the solid on the yz-plane is equal to the complement of half the dihedral angle measured at the triple line between the twinned solid, untwinned solid and liquid.…”
Section: Boundary Conditions and Solidification Parametersmentioning
confidence: 99%
“…More confusion has been brought recently by Li et al [13], who observed that the application of a static magnetic field of only 0.2 T, which is supposed to weaken convection, induces the formation of twinned dendrites in Al-Fe and Al-Zn alloys in small DC cast ingots. Finally, although twinned dendrites have a growth advantage over regular dendrites under the above-mentioned conditions, there is still some uncertainty about their tip morphology [3,12,[14][15][16][17][18]. More important, nothing is known about twin nucleation.…”
Section: Introductionmentioning
confidence: 99%